PENERAPAN KEGIATAN LITERASI DALAM PEMBELAJARAN SEJARAH PADA KELAS X SMAN 1 JAWAI - Rusmida; Ika Rahmatika Chalimi; Astrini Eka Putri (LPPM Universitas Cipta Mandiri, 2025)
This research aims to describe the implementation of literacy activities in history lessons for grade X at SMAN 1 Jawai. This research employs a descriptive qualitative approach. Data collection methods used observation, interviews with history teachers and students, and documentation. The data analysis techniques used involve data reduction, data presentation, and decision-making. The results showing that the teacher has implemented literacy activities, particularly reading literacy, which includes various literacy aspects such as reading texts from both books and teacher-prepared materials, group discussions of texts, presentations, and Q&A sessions. The process of implementing literacy activities involves planning, execution, and evaluation, adhering to literacy learning principles such as pre-reading, reading, and post-reading activities. However, the implementation of literacy activities faces several challenges, notably a lack of student interest in reading and limited resources such as books and technology.